PENGEMBANGAN MEDIA PEMBELAJARAN FLIPBOOK FISIKA UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK - Sri Hayati; Agus Setyo Budi; Erfan Handoko (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
This study was carried out to generate media Flipbook Physics-based learning in the form of multimedia. The study was conducted in the laboratory of physical education for the development phase and in SMAN 22 Jakarta Timur for field testing phase media use Flipbook Physics. The method used is the Research and Development and refers to the development model ADDIE (Analysis, Design, Development, Implementation, and Evaluation). Physics flipbook display using 3D software PageFlip Professional 1.7.6. that content is backed up with some software, such as AVS Video Editor, iSpring Suite 6, photoshop, and pdf. Physics Flipbook feasibility test results conducted by experts on the matter and media, also validated by the user. Results of media experts, namely 91.46%, from 94.17% matter experts and the results of tests on users gained 99.38% from 96.70% of the educators and learners. Flipbook Physics validated then used to obtain the data from the experimental class. The average percentage of all aspects of an increase of 57.23%. It can be concluded that the overall Flipbook Physics-based multimedia can enhance learning outcomes of students in high school. Keywords: Development, Flipbook Physics, Learning Outcomes, 3D PageFlip Professional.